2019
DOI: 10.1111/apha.13328
|View full text |Cite
|
Sign up to set email alerts
|

Adult vascular dysfunction in foetal growth‐restricted guinea‐pigs is associated with a neonate‐adult switching in Nos3 DNA methylation

Abstract: Aim Foetal growth restriction (FGR) is associated with endothelial dysfunction and cardiovascular diseases in adult subjects. Early vascular remodelling and epigenetic changes occurring on key endothelial genes might precede this altered vascular function. Further, it has been proposed that oxidative stress during development may determine some of these epigenetic modifications. To address this issue, we studied the in vivo and ex vivo vascular function and Nos3 promoter DNA methylation in arteries from eight‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The contractile and relaxing responses in FGR guinea pig arteries, both carotid and femoral, followed a pattern of accelerated aging, an effect that was evident since late gestation in femoral arteries but not in carotid vessels. Notably, the changes in NO-mediated responses occurred parallel to life-course modifications in eNOS expression and activation [40,41]. Comparable studies in fetal growth-restricted rats have shown sex-specific early aging in the vascular responses of mesenteric arteries, occurring in females but not in male offspring [23,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contractile and relaxing responses in FGR guinea pig arteries, both carotid and femoral, followed a pattern of accelerated aging, an effect that was evident since late gestation in femoral arteries but not in carotid vessels. Notably, the changes in NO-mediated responses occurred parallel to life-course modifications in eNOS expression and activation [40,41]. Comparable studies in fetal growth-restricted rats have shown sex-specific early aging in the vascular responses of mesenteric arteries, occurring in females but not in male offspring [23,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that FGR, in human and animal models, results in comparable epigenetic changes in the endothelium. For instance, a similar epigenetic effects occurs in the gene coding for eNOS ( NOS3 or Nos3 ) in human [43,44], guinea pig [40,41], and rat [45] FGR endothelial cells. Conversely, LINE-1 has been suggested to correlate with aging, cardiovascular risk, and metabolic dysfunction in humans [46,47,48,49,50], conditions prompted by an impaired fetal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Foetal growth restriction is associated with, among other pathologies, vascular dysfunction later in life. 2 Krause et al 17 showed recently how altered vessel structures developing during the foetal period persist and precede this altered vascular function in adult life.…”
Section: Pregnancymentioning
confidence: 99%
“…A decrease in uteroplacental perfusion due to increased vascular resistance leads to ischemic reperfusion injury and/or hyperoxia/reoxygenation, the production of excessive amounts of reactive oxygen species (ROS) and uncontrolled oxidative stress (OS) [ 5 , 6 ]. The latter can play a central role in programming the long-term consequences of the development of cardiovascular diseases in the fetus: an increase of superoxide and nitric oxide production with the formation of prooxidant peroxy-nitrite under OS leads to vascular dysfunction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%